Analyse d’un genre de discours spécialisé : les lettres annuelles de Warren Buffett aux actionnaires de Berkshire Hathaway et leur spécificité - Catherine RESCHE (E-REA)
The paper focuses on a particular genre which is characteristic of the corporate world. Warren Buffett’s letters to the shareholders seem to arouse unprecedented interest among readers who greatly outnumber his shareholders. The letters’ form and content were analyzed quantitatively and qualitatively and compared to a sample corpus of other letters to the shareholders in order to determine their specificity. The diachronic approach that was chosen was an opportunity to observe how Buffett’s letters have evolved over a period of 32 years. The findings of this analysis seem to indicate that the letters have a dialogic dimension and that the author is much more present in his discourse than others. The atypical stylistic patchwork that characterizes Buffett’s style suggests that the letters as a whole can be considered as macro-speech acts. Yet, in spite of their divergences from the usual style, Buffett’s letters can clearly be identified as instances of the genre because of the context in which they were produced, the aim that was pursued and the social role they perform as a rule. For the very same reasons, they can be regarded as a sample of specialized discourse, even though they use no specific syntax and contain no great amount of sophisticated technical language.